Epigenetic diversity of Saccharum spp. accessions assessed by methylation-sensitive amplification polymorphism (MSAP) - Martins, Alessandra Alves [UNESP]; Silva, Marcel F. da; Pinto, Luciana Rossini (Springer, 2020)
The epigenetic diversity of six genotype groups (commercial cultivars, S. officinarum, S. spontaneum, S. robustum, S. barberi, and Erianthus sp.) was assessed through methylation-sensitive amplification polymorphism (MSAP). A total of 1341 MSAP loci were analyzed, of which 1117 (83.29%) were susceptible to cytosine methylation and responsible for a higher proportion of overall diversity among genotypes. The MSAP selective primer combinations captured different proportions of internal and external cytosine methylation loci across genotype groups, while the average external cytosine frequency was higher for all genotype groups. The genotypes were divided into two subpopulations with a high differentiation index (phi st = 0.086) based on epigenetic loci. The genotypes were clustered in three subgroups for both methylated and unmethylated loci, considering dissimilarity values. Four methylated fragments (MFs) were randomly selected and subsequently sequenced and compared with sugarcane public databases using BLASTN. MF alignments suggest that cytosine methylation occurs in sugarcane near CpG islands and tandem repeats within transcribed regions and putative cis-regulatory sequences, which assigned functions are associated with stress adaptation. These results provide the first insights about the distribution of this epigenetic mark in sugarcane genome, and suggest a biological relevance of methylated loci.
Keywords: Saccharum spp; Wild accessions; Cytosine methylation; Epigenome diversity